(untitled) (Altre Modernità, 2013)
Jorge Eduardo Eielson is a well-known poet and plastic artist, but his narrative works remain little-known, even in his native Peru. El cuerpo de Giulia-no is a discontinous and elusive text. Written in the 1950s but not published until 1971 in Mexico, it is an undoubtedly innovative work which thwarts the readers’s expectations with its fragmentary composition, elliptical tendencies, and the underlying dislogue amongst literature, visual arts and science running throughout the text. Like a typical Eislson work, it is a ‘chaotic’ text, which brings together the themes of the indigenist conflict and the Apocalypse emboded by the crisis of language with elements of meta-theatre and science fiction. I focus on the parody of science fiction within the novel. The world of the future, that anticipated in science fiction, is, for Eielson, the present world. Thus he represents, in the contemporary context, the cultural conflict with the indigenous world though a sort of ‘alien’ invasion (indigenous people) which is controlled and repressed, the origins of which can be found in the history of Peru. However, through this sort of ‘ontological break’, Eielson let us see the first steps toward the foundation of a new order out of chaos.